Théologie et sciences des religions : l’apport de Karl Barth - Anthony Feneuil (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Can a theological work have a place in religious studies ? Through the examination of some major concepts of Barth’s theology, and particularly of his understanding of the relation between revelation and religion, I will show that it is possible to argue for such an intrusion of theology within the field of the scientific study of religion, as much from a theological point of view as from a scientific point of view. Theology could even become an unexpected resource for epistemological reflection on religious studies.